TINGKAT ERODIBILITAS TANAH PADA BEBERAPA TINGKAT KEMIRINGAN LAHAN DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Kalaati, Ismail; Ramlan, Ramlan; Rahman, Abd. (AGROTEKBIS, 2019)
This study aimed at determining erosion rate under several lands with different slopes in Labuan village, Toposo sub-district of Donggal district. This research was expected to produce information that could be used as consideration for achieving optimal plant yield. It was conducted from November to December 2016. Soil samples were analyzed in the Soil Laboratory of Agriculture Faculty Tadulako University of Palu. Survey was done on each land unit resulting from overlaying topography map and land use map. Soil samples for each land unit were determined purposively. Highest erosion rate of 0.61 ton/ha/yr categorized as high was found in cacao plantation of 15-25% slope whereas lowest of 0.32 ton/ha/yr categorized was in cacao plantation of 8-15% slope. Lack of organic matter in this cacao plantation is the main cause of soil erosion.